Functionalized graphene, quantum dots, and PEDOT:PSS based screen-printed electrode for the endocrine disruptor bisphenol A determination - dos Santos, Anderson M. (2024)
Strategies aimed for the monitoring the endocrine disruptor bisphenol A (BPA) become essential due to the high toxicity that this substance can cause in the environment. In this sense, a screen-printed electrode with functionalized graphene, cadmium telluride quantum dots, and polymer (PEDOT:PSS) was manufactured for the determination of the BPA in environmental matrices. The materials that compose the sensor were characterized by fluorescence spectroscopy, X-ray diffraction, FEG-SEM, TEM and FTIR. The electrochemical behavior of the analyte was performed by cyclic voltammetry and the quantification by square-wave voltammetry, respectively. The electroanalytical method showed a linear response in the BPA concentration range from 0.020 to 9.0 µmol L−1 with a limit of detection of 3.4 nmol L−1. Finally, the electroanalytical method was successfully applied to environmental samples for the determination of BPA, with a recovery close to 100%. This demonstrates its good applicability and sensitivity for this type of sample.